Three-dimensional spherical discontinuous deformation analysis using second-order cone programming. (August 2019) - Meng, Jingjing; Cao, Ping; Huang, Jinsong; Lin, Hang; Li, Kaihui; Cao, Rihong
Abstract: In this paper, a new formulation of three-dimensional spherical discontinuous deformation analysis (DDA) based on second-order cone programming has been proposed. Artificial springs with open-close iteration used in classic DDA have been removed, given that improper stiffness parameters might cause numerical problems. Furthermore, to account for irregular granular shapes, a rolling resistance model is incorporated in the variational formulation. The proposed formulation can be cast into a standard second-order cone programming program, which can be solved using efficient off-the-shelf optimisation solvers. The proposed approach is validated by a series of numerical examples.